Patient Counseling Tools for Improving Adherence to Antiretroviral Therapy - B.A, Srikanth; K.R, Purushothama; K.R, Narotham (Indian Journal of Pharmacy Practice)
Patient counseling were intended to improve adherence and maintaining quality of life. Antiretroviral adherence is the second strongest predictor of progression to AIDS and death, after CD4 count. Incomplete adherence to ART is common in all groups of treating individuals. The commonest cause of ART failure is poor adherence. Several factors associated with poor adherence include a poor patient-clinician relationship, high pill burden, forgetfulness, mental depression, lack of patient education, inability of patients to identify their medications, drug toxicity, beliefs about treatment and the impression of being too ill for treatment. Counseling steps include establishing the rapport between the patient and pharmacist, developing individual treatment plan and using of information sheets, compliance aids, leaflets can be helpful in better understanding about the ART regimen they are taking. The key to successful is educating the patient before the initiation of therapy, supporting ART initiation as the patient first starts taking medications, and continuously monitoring and supporting adherence. Using of adherence devices like pill boxes, reminders and visual medication schedules can improve the adherence towards the antiretroviral drugs and can improve the outcome in HIV patient receiving ART.
Keywords: Antiretroviral therapy; Adherence; Patient Counseling; quality of life; HIV; India